1980
DOI: 10.1111/j.1471-6402.1980.tb00955.x
|View full text |Cite
|
Sign up to set email alerts
|

Images of Men and Women: A Comparison of Feminists and Nonfeminists

Abstract: It was hypothesized that feminists would evaluate male-and femaledefined traits differently than would nonfeminists and that feminists would rate fewer traits as descriptive of only one sex. Undergraduates rated a set of adjectives for appropriateness t o men and women, and for social desirability. Dempewolff's (1973) Feminism II Scale was given to dichotomize the sample into feminists and nonfeminists. The feminists 0361-6843/80/16OO-O186$00.95 0 1980 Human Sciences Press

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…It has been found that often stereotypically masculine attributes are considered more essential for work success (Bernard, 1979;Rapin and Cooper, 1980). As an explanation for some of their findings, Powers-Alexander, Galvin, Lambert, Speth & Plake (1983) voiced the suspicion that even the most positive feminine attributes may not be as highly valued as masculine attributes in most employment situations.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that often stereotypically masculine attributes are considered more essential for work success (Bernard, 1979;Rapin and Cooper, 1980). As an explanation for some of their findings, Powers-Alexander, Galvin, Lambert, Speth & Plake (1983) voiced the suspicion that even the most positive feminine attributes may not be as highly valued as masculine attributes in most employment situations.…”
Section: Introductionmentioning
confidence: 99%